2018
DOI: 10.1001/jamanetworkopen.2018.1588
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Buprenorphine-Naloxone and Opioid Pain Reliever Prescriptions After the Affordable Care Act Medicaid Expansion

Abstract: Key Points Question Did Medicaid expansion under the US Affordable Care Act change prescription fills for buprenorphine with naloxone, a treatment for opioid use disorder, and opioid pain relievers? Findings In this cohort study using difference-in-differences analysis of all-payer prescription fill data from 5 states, Medicaid expansion was associated with a significant overall increase in people filling prescriptions for buprenorphine with naloxone. Expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 24 publications
4
66
1
Order By: Relevance
“…Our results are robust to a number of specifications and a falsification test. This finding is similar to Sharp et al () and Saloner et al () whose analyses of Medicaid prescribing data indicate that there was no effect of Medicaid expansion on prescription opioid use. One possible explanation for these findings is that the two opposing effects (increased access and increased treatment) wash each other out.…”
Section: Resultssupporting
confidence: 89%
“…Our results are robust to a number of specifications and a falsification test. This finding is similar to Sharp et al () and Saloner et al () whose analyses of Medicaid prescribing data indicate that there was no effect of Medicaid expansion on prescription opioid use. One possible explanation for these findings is that the two opposing effects (increased access and increased treatment) wash each other out.…”
Section: Resultssupporting
confidence: 89%
“…10,29 Recent evidence demonstrates that compared with nonexpansion states, Medicaid expansion states experienced increases in overall prescriptions for, Medicaidcovered prescriptions for, and Medicaid spending on both MOUDs, particularly buprenorphine and naltrexone, and the opioid overdose reversal medication naloxone. [6][7][8]11,14,30,31,35 Two prior studies 12,16 have found associations between income eligibility expansions for…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that uptake of medications for opioid use disorder (MOUDs), including methadone, buprenorphine, and extended-release naltrexone, has increased more in expansion states compared with nonexpansion states. [6][7][8][9][10][11] These medications (often in combination with counseling and behavioral therapies) have been linked to improvements in treatment retention and OUD remission as well as reductions, in some cases as high as 50%, in all-cause and overdose-related mortality. 12,13 Medicaid-reimbursed prescriptions for the opioid overdose reversal medication naloxone have also increased significantly more in expansion states compared with nonexpansion states.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence demonstrates that compared to non-expansion states, Medicaid expansion states experienced increases in overall prescriptions for, Medicaid-covered prescriptions for, and Medicaid spending on evidence-based OUD pharmacotherapies, particularly buprenorphine and naltrexone. [33][34][35][36] Some limitations and future directions are noteworthy. First, although buprenorphine distribution was increasing overall, examination of individual 3-digit zip codes indicates that the opposite pattern may be occurring in some rural areas.…”
Section: Discussionmentioning
confidence: 99%